SOCIAL NETWORK IN MOTHER GODDESS WORSHIP: A CASE STUDY OF MEDIUM DANG THI MAT, HANG PAGODA-QUAN TAM TEMPLE, THANH MY COMMUNE, SON TAY TOWN, HANOI - Nguyen, Thi Minh Thu (Trường Đại học Đà Lạt, 2023)
Many authors, domestic and foreign, have studied different aspects of Mother Goddess worship. Studying Mother Goddess worship on the basis of  social network theory is a modern research trend, and is valuable in determining the complexity of social relationships that people build, maintain, and develop in their real lives as members of society. This article adopts some points of view in social network theory to study a specific social network in Mother Goddess worship, that of medium Dang Thi Mat, of Hang Pagoda-Quan Tam Temple, Thanh My Commune, Son Tay Town, Hanoi to clarify the characteristics, structure, homophily, operating principles, and development of this social network in modern society. The analysis in the article is based on long-term fieldwork (2015-2018), observations, and in-depth interviews with many individuals to obtain objective and tangible research results.